2017
DOI: 10.1177/1010428317725834
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic role of mismatch repair gene defect in endometrial cancer patients

Abstract: The study was to evaluate the prevalence of mismatch repair gene defect among Thai patients with endometrial cancer and its association with clinico-pathological features and survivals. The formalin fixed paraffin-embedded blocks of EMC tissue from hysterectomy specimens of patients having surgery in our institution between 1 Jan 1995 and 31 December 2016 were assessed for the immunohistochemical expression of 4 mismatch repair proteins (MLH1, PMS, MSH2, MSH 6). Mismatch repair gene defect was determined by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…Findings have varied from subsequent studies of varying design assessing survival using multivariate analysis: no association was detected between tumor MMR-deficiency and survival from analysis of 109 EC patients (endometrioid and non-endometrioid subtypes; MSI-H=0.46; 95% CI=0.05–4.77) [ 33 ], improved survival (HR=0.2; 95% CI=0.1–0.7) was reported for MMR-deficient EC based on IHC results from 191 EC patients [ 24 ]; no association between tumor MMR class and outcome was observed for 1,024 patients designated as epigenetic MMR defective EC (HR=0.78; 95% CI=0.43–1.41) or “probable MMR mutation” (HR=0.91; 95% CI=0.40–2.07) [ 18 ]. The most recent study of 466 women reported that endometrioid MLH1 -methylated MMR-deficient EC cases had significantly reduced recurrence-free survival in univariate analysis (p<0.001) [ 22 ]; a recent study of 385 Thai women reported improved survival for patients exhibiting tumor MMR deficiency [ 34 ], although it should be noted that MMR loss of function was observed for a relatively large proportion of their cohort (55%, 33% ascribed to loss of MLH1 function) compared to what has been previously reported for largely Caucasian cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Findings have varied from subsequent studies of varying design assessing survival using multivariate analysis: no association was detected between tumor MMR-deficiency and survival from analysis of 109 EC patients (endometrioid and non-endometrioid subtypes; MSI-H=0.46; 95% CI=0.05–4.77) [ 33 ], improved survival (HR=0.2; 95% CI=0.1–0.7) was reported for MMR-deficient EC based on IHC results from 191 EC patients [ 24 ]; no association between tumor MMR class and outcome was observed for 1,024 patients designated as epigenetic MMR defective EC (HR=0.78; 95% CI=0.43–1.41) or “probable MMR mutation” (HR=0.91; 95% CI=0.40–2.07) [ 18 ]. The most recent study of 466 women reported that endometrioid MLH1 -methylated MMR-deficient EC cases had significantly reduced recurrence-free survival in univariate analysis (p<0.001) [ 22 ]; a recent study of 385 Thai women reported improved survival for patients exhibiting tumor MMR deficiency [ 34 ], although it should be noted that MMR loss of function was observed for a relatively large proportion of their cohort (55%, 33% ascribed to loss of MLH1 function) compared to what has been previously reported for largely Caucasian cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Although dMMR has been associated with a better prognosis in CRC, its prognostic significance in EC is unclear. 21 Whereas many studies have reported worse survival and/or shorter disease-free survival among patients dMMR or microsatellite instability (MSI), 10,14,[22][23][24][25] other studies have demonstrated improved survival [26][27][28][29] or no association. [30][31][32][33] A recent meta-analysis also demonstrated no association between MMR status and OS or RFS.…”
Section: Discussionmentioning
confidence: 99%
“…Such risks are well recognized in Western populations [11]. Notably, only few studies in Asia have been published [12131415]. Our study found the prevalence of MMR gene defect in Thai patients as high as 55% [15].…”
mentioning
confidence: 61%
“…Notably, only few studies in Asia have been published [12131415]. Our study found the prevalence of MMR gene defect in Thai patients as high as 55% [15]. This should alert the gynecologic oncologist to assess this particular risk by comprehensive history taking focused on previous and family history.…”
mentioning
confidence: 66%